Treatment of Nonalcoholic Steatohepatitis: A Review - Mukherjee, Sandeep (Technological Innovation in Pharmaceutical Research Vol. 7, 2021)
Nonalcoholic steatohepatitis is a metabolic dysfunction-related liver disease that has become one of the leading causes of cirrhosis and liver transplantation in the United States.Obesity and insulin resistance are the two most common risk factors for nonalcoholic steatohepatitis, with patients frequently exhibiting metabolic syndrome symptoms. Patients who are able to modify these risk factors and are recognised early in the course of their disease can experience histological improvement, including fibrosis arrest or improvement. In addition to the development of cirrhosis and its life-threatening complications such as hepatocellular carcinoma, variceal bleeding, ascites, and hepatic encephalopathy, nonalcoholic steatohepatitis is associated with coronary artery, carotid artery, and peripheral vascular disease, with coronary artery disease being the most common cause of death. Despite the completion of several clinical trials assessing a variety of drugs targeted at different parts of nonalcoholic steatohepatitis development and progression, there is presently no approved treatment for this condition other than risk factor management. However, several promising clinical trials are in progress and the future looks promising. The most recent and salient medical advances in the treatment of nonalcoholic steatohepatitis will be discussed in this article.